Understanding project stakeholders' perceptions of public participation in China's infrastructure and construction projects: Social effects, benefits, forms, and barriers. Issue 2 (11th March 2014) - Xie, Lin-lin; Yang, Yu; Hu, Yi; P.C. Chan, Albert
Abstract : Purpose: – Public participation has been implemented with growing frequency as an instrument for dealing with the increased socio-economic and environmental disputes in public infrastructure and construction (PIC) projects in China. The purpose of this paper is to examine the perceptions of major stakeholders on the major aspects related to public participation practices in China's PIC projects and intends to convey what is presently happening in this segment of the construction industry. Design/methodology/approach: – Specific topics of the social effects, benefits, forms, and barriers were addressed through a recent survey of the major stakeholders involved in PIC projects. The survey results were used to perform a strength-weakness-opportunity-threat analysis for evaluating the status quo of public participation in PIC projects. Findings: – The survey results indicate that the development of public participation practices in China remains relatively slow despite the urgent need to promote this mechanism for solving socio-economic and environmental disputes in PIC projects. Thus, a four-step strategic plan is suggested to be established to overcome main barriers for the implementation of public participation and promote its development in China. Originality/value: – This study aims to evaluate the status quo of the public participation practices in China by conducting a national survey, which has never been conducted before. The findings of this paper provide a holistic view of the status quo of public participation in China's PIC projects and promote a better application of this mechanism in the construction industry.